Dodecahedral co3o4 particle array foam copper-based catalyst and preparation method and application thereof

CN118384884BActive Publication Date: 2026-10-16HENAN UNIVERSITY OF TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410187746.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-20
Publication Date
2026-10-16
Estimated Expiration
2044-02-20

AI Technical Summary

Technical Problem

[0008]为了解决现有技术由于传统的整体式催化剂在反应过程中会发生活性物质的迁移和烧结,在工业应用中受到了很大限制的问题,本发明提供一种十二面体Co3O4颗粒阵列泡沫铜基催化剂及其制备方法和应用,本发明制得的催化剂,其表面活性物质钴和泡沫铜载体两个不同金属之间产生金属-载体的强相互作用,使得催化剂的氧化还原能力增强以及表面具有更多的活性氧,提高了催化剂用于甲苯气体催化燃烧时的催化效果

Benefits of technology

[0025] Beneficial effects: The catalyst obtained by the preparation method of the present invention enables a strong metal-support interaction between the surface active material cobalt and the foamed copper support, which enhances the redox ability of the catalyst and provides more active oxygen on the surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118384884B_ABST
    Figure CN118384884B_ABST
Patent Text Reader

Abstract

The application provides a dodecahedral Co3O4 particle array foam copper-based catalyst and a preparation method and application thereof. The catalyst prepared by the application has strong metal-support interaction between the surface active substance cobalt and the foam copper carrier of two different metals, so that the redox capacity of the catalyst is enhanced, and the surface has more active oxygen, and the catalytic effect of the catalyst for catalytic combustion of toluene gas is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of waste gas treatment technology, specifically to a dodecahedral Co3O4 particle array foam copper-based catalyst, its preparation method, and its application. Background Technology

[0002] Rapid industrialization has exacerbated air pollution, with volatile organic compounds (VOCs) being a significant source of air pollutants, seriously harming the environment and health. VOCs are diverse, including aliphatic, aromatic (benzene, toluene, etc.), alcohols / aldehydes / ketones / esters, and halogenated compounds. Among these, aromatic ring hydrocarbons, as common chemical raw materials and solvents, pose a significant threat to human health. Therefore, the treatment and removal of benzene series compounds is of great importance. To reduce VOC emission concentrations, various VOC treatment technologies exist, such as adsorption, absorption, membrane separation, and catalytic combustion. Catalytic combustion decomposes organic molecules like benzene into smaller, non-polluting molecules (H2O and CO2). This method, with its high efficiency and lack of secondary pollution, is considered the most promising technology for treating VOC exhaust gases.

[0003] The core of catalytic combustion technology development lies in the preparation and research of catalysts. Currently, existing catalysts can be broadly classified into two categories: noble metal catalysts and non-noble metal catalysts. Research on noble metal catalysts mainly focuses on precious metals such as Pd, Pt, Au, and Ag. However, the high cost, susceptibility to poisoning, and sintering issues of noble metal catalysts have limited their development. Therefore, transition metals, due to their abundant reserves, low cost, and excellent catalytic activity, have gradually become a research hotspot.

[0004] Currently, most catalysts used in industry are monolithic catalysts, with some being powder catalysts. Compared to powder catalysts, monolithic catalysts have advantages such as lower pressure drop, more uniform heat transfer, and more stable structure. Therefore, monolithic catalysts have a more promising future in practical applications. Traditional monolithic catalysts load the active material onto the surface of cordierite honeycomb ceramic (2MgO·2Al2O3·5SiO2). However, this type of traditional monolithic catalyst is subject to migration and sintering of the active material during the reaction process, which greatly limits its industrial applications.

[0005] Patent CN105688904A provides an integral catalyst for the catalytic combustion of toluene. The catalyst requires a reaction temperature of 230°C when the toluene conversion rate is 90%. Although the reaction temperature is not high, the catalyst used is a precious metal catalyst, which makes the production cost of the catalyst high.

[0006] Patent CN106902838A provides an integral composite catalyst for the catalytic combustion of VOCs, which is prepared by loading active substances such as Cr2O3, CuO, MnO2, LaO3, and TiO2 onto cordierite. This catalyst reaches a reaction temperature of 332℃ when the toluene conversion rate is 90%, indicating poor catalyst performance.

[0007] Patent CN110783115A discloses a method for preparing a manganese dioxide / carbon / foam metal composite material. The method involves first mixing a cobalt nitrate hexahydrate solution and a dimethylimidazole solution to prepare ZIF-67, and then impregnating the pretreated foam metal into the mixed solution. This method, which loads ZIF-67 via impregnation, suffers from problems such as low loading and uneven loading, resulting in low catalytic activity. Summary of the Invention

[0008] To address the problem that existing monolithic catalysts suffer from migration and sintering of active materials during the reaction process, which greatly limits their industrial applications, this invention provides a dodecahedral Co3O4 particle array foam copper-based catalyst, its preparation method, and its application. The catalyst prepared by this invention exhibits strong metal-support interactions between the surface active material cobalt and the foam copper support, which enhances the catalyst's redox capacity and increases the amount of active oxygen on its surface, thereby improving the catalytic effect of the catalyst when used for the catalytic combustion of toluene gas.

[0009] The technical solution adopted by this invention to solve the above-mentioned technical problems is as follows: a method for preparing a dodecahedral Co3O4 particle array foam copper-based catalyst, comprising the following steps:

[0010] (1) Dissolve Co(NO3)2·6H2O, NH4F and CH4N2O in deionized water to obtain a mixed solution. Transfer the copper foam and the above mixed solution to a reactor for hydrothermal reaction to obtain Co-modified@CF.

[0011] (2) Co-modified@CF was pyrolyzed under an inert atmosphere to obtain CoO@CF;

[0012] (3) Dissolve 2-MIM in deionized water and anhydrous ethanol to obtain a mixed solution. Add CoO@CF to the above mixed solution for soaking treatment. After soaking, take it out, wash and dry it to obtain ZIF-67@CF-H.

[0013] (4) ZIF-67@CF-H was calcined in air to obtain a dodecahedral Co3O4 particle array foam copper-based catalyst.

[0014] As a further optimization of the preparation method of a dodecahedral Co3O4 particle array foam copper-based catalyst: the molar ratio of the added Co(NO3)2·6H2O, NH4F and CH4N2O in step (1) is 1:3.5~4.5:4.5~5.5.

[0015] As a further optimization of the preparation method of the dodecahedral Co3O4 particle array foam copper-based catalyst: the foam copper used in step (1) is pretreated foam copper, and the pretreatment specifically includes:

[0016] The copper foam was placed in an HCl solution, sonicated, washed several times with deionized water and ethanol, and then dried.

[0017] As a further optimization of the preparation method of a dodecahedral Co3O4 particle array foam copper-based catalyst: the concentration of the HCl solution used in the pretreatment is 0.1 mol / L, the ultrasonic time is 15 min, the drying temperature is 60℃, and the drying time is 2 h.

[0018] As a further optimization of the preparation method of the dodecahedral Co3O4 particle array foam copper-based catalyst: the hydrothermal reaction in step (1) is specifically as follows:

[0019] After mixing the mixed solution with the pretreated copper foam, the mixture was transferred to a high-pressure reactor with a polytetrafluoroethylene liner. The reaction temperature was controlled at 110–130°C and the reaction time was 10–14 h. After the reaction was completed, the mixture was cooled to room temperature, washed with deionized water and dried at 60°C for 2 h.

[0020] As a further optimization of the preparation method of a dodecahedral Co3O4 particle array foam copper-based catalyst: the inert atmosphere in step (2) is nitrogen atmosphere, the pyrolysis temperature is 320-350℃, the pyrolysis time is 1h, and the pyrolysis heating rate is 3℃ / min.

[0021] As a further optimization of the preparation method of a dodecahedral Co3O4 particle array foam copper-based catalyst: in step (3), the molar ratio of deionized water and ethanol is 1:1, the soaking time is 12h, the drying temperature is 60℃, and the drying time is 2h.

[0022] As a further optimization of the preparation method of a dodecahedral Co3O4 particle array foam copper-based catalyst: the calcination temperature in step (4) is 350℃, the calcination time is 3h, and the calcination heating rate is 3℃ / min.

[0023] The technical solution adopted by the present invention to solve the above-mentioned technical problems is: a foam copper-based catalyst with a dodecahedral Co3O4 particle array, which is prepared by the above method.

[0024] The technical solution adopted by the present invention to solve the above-mentioned technical problems is: the application of a dodecahedral Co3O4 particle array foam copper-based catalyst, and the application of the above catalyst in the catalytic combustion of toluene gas.

[0025] Beneficial effects: The catalyst obtained by the preparation method of the present invention enables a strong metal-support interaction between the surface active material cobalt and the foamed copper support, which enhances the redox ability of the catalyst and provides more active oxygen on the surface.

[0026] The catalyst prepared by this invention improves the catalyst loading. By sacrificing the metal-organic framework ZIF-67, the presence of the dodecahedral Co3O4 particle array increases its specific surface area and pore volume, which is beneficial for the catalytic combustion of toluene gas and also has good stability.

[0027] The present invention uses transition metal salts in the preparation of dodecahedral Co3O4 particle array foam copper-based catalysts. Compared with precious metal raw materials, the raw materials are cheaper. The catalyst synthesis reaction temperature is low, the reaction is mild and easy to control, the catalyst calcination temperature is low and the energy consumption is low. Attached Figure Description

[0028] Figure 1 This is a graph showing the functional relationship between the catalyst activity and temperature. Figure 2 This is a graph showing the long-term stability test results of a dodecahedral Co3O4 particle array foam copper-based catalyst. Figure 3 The figure shows the cycle stability test results of the dodecahedral Co3O4 particle array foam copper-based catalyst. Figure 4 SEM image of a dodecahedral Co3O4 particle array foam copper-based catalyst; Figure 5 SEM image of a dodecahedral Co3O4 particle array foam copper-based catalyst; Figure 6 SEM image of a dodecahedral Co3O4 particle array foam copper-based catalyst; Figure 7 The image shows the SEM results of the CF catalyst. Figure 8 The image shows the SEM results of the CF catalyst. Detailed Implementation

[0029] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. Parts not described or disclosed in detail in the following embodiments of the present invention should be understood as prior art known or should be known by those skilled in the art.

[0030] A method for preparing a dodecahedral Co3O4 particle array foam copper-based catalyst includes the following steps:

[0031] (1) Dissolve Co(NO3)2·6H2O, NH4F and CH4N2O in deionized water to obtain a mixed solution. Transfer the copper foam and the above mixed solution to a reactor for hydrothermal reaction to obtain Co-modified@CF.

[0032] (2) Co-modified@CF was pyrolyzed under an inert atmosphere to obtain CoO@CF;

[0033] (3) Dissolve 2-MIM in deionized water and anhydrous ethanol to obtain a mixed solution. Add CoO@CF to the above mixed solution for soaking treatment. After soaking, take it out, wash and dry it to obtain ZIF-67@CF-H.

[0034] (4) ZIF-67@CF-H was calcined in air to obtain a dodecahedral Co3O4 particle array foam copper-based catalyst.

[0035] This invention uses copper foam as a carrier and grows a metal-organic framework ZIF-67 in situ as a precursor through hydrothermal reaction, pyrolysis reaction and soaking. Then, the ZIF-67 precursor is sacrificed by calcination to obtain Co3O4 metal oxide, thus preparing a copper foam-based catalyst with a dodecahedral Co3O4 particle array.

[0036] A dodecahedral Co3O4 particle array foam copper-based catalyst, which is prepared by the above method.

[0037] Application of a dodecahedral Co3O4 particle array foam copper-based catalyst, specifically its application in the catalytic combustion of toluene gas.

[0038] Example 1

[0039] A method for preparing a dodecahedral Co3O4 particle array foam copper-based catalyst includes the following steps:

[0040] (1) Dissolve Co(NO3)2·6H2O, NH4F and CH4N2O in deionized water to obtain a mixed solution. Transfer the copper foam and the above mixed solution to a reactor for hydrothermal reaction to obtain a pink flake sample Co-modified@CF.

[0041] The molar ratio of Co(NO3)2·6H2O, NH4F, and CH4N2O added was 1:4:5. In this embodiment, the amount of Co(NO3)2·6H2O used was 2 mmol, the amount of NH4F used was 8 mmol, the amount of CH4N2O used was 10 mmol, and the amount of deionized water used was 15 mL. The foamed copper used was pretreated. The pretreatment process was as follows: the foamed copper was placed in an HCl solution, ultrasonically treated, washed several times with deionized water and ethanol, and then dried. The concentration of the HCl solution used in the pretreatment was 0.1 mol / L, the ultrasonic time was 15 min, the drying temperature was 60℃, and the drying time was 2 h. The selected foamed copper had a pore density of 110 ppi, a diameter of 18 mm, and a thickness of 1.8 mm.

[0042] The hydrothermal reaction is specifically as follows:

[0043] The mixed solution was mixed with pretreated copper foam and then transferred to a high-pressure reactor with a polytetrafluoroethylene liner. The reaction temperature was controlled at 120℃ and the reaction time was 12h. After the reaction was completed, the mixture was cooled to room temperature, washed with deionized water and dried at 60℃ for 2h.

[0044] (2) Co-modified@CF was pyrolyzed under an inert atmosphere to obtain a black flake sample CoO@CF, wherein the inert atmosphere was nitrogen atmosphere, the pyrolysis temperature was 350℃, the pyrolysis time was 1h, and the pyrolysis heating rate was 3℃ / min.

[0045] (3) Dissolve 2-MIM in deionized water and anhydrous ethanol to obtain a mixed solution. Add CoO@CF to the above mixed solution for soaking treatment. After soaking, take it out, wash and dry it to obtain ZIF-67@CF-H. The molar ratio of deionized water to ethanol is 1:1, the soaking time is 12h, the drying temperature is 60℃, and the drying time is 2h. In this example, the amount of 2-MIM used is 2mmol, the amount of deionized water used is 5mL, and the amount of anhydrous ethanol used is 5mL.

[0046] (4) ZIF-67@CF-H was calcined in air to obtain a dodecahedral Co3O4 particle array foam copper-based catalyst, wherein the calcination temperature was 350℃, the calcination time was 3h, and the calcination heating rate was 3℃ / min.

[0047] Example 2

[0048] A method for preparing a dodecahedral Co3O4 particle array foam copper-based catalyst includes the following steps:

[0049] (1) Dissolve Co(NO3)2·6H2O, NH4F and CH4N2O in deionized water to obtain a mixed solution. Transfer the copper foam and the above mixed solution to a reactor for hydrothermal reaction to obtain a pink flake sample Co-modified@CF.

[0050] The molar ratio of Co(NO3)2·6H2O, NH4F, and CH4N2O added was 1:3.5:4.5. In this embodiment, the amount of Co(NO3)2·6H2O used was 2 mmol, the amount of NH4F used was 8 mmol, the amount of CH4N2O used was 10 mmol, and the amount of deionized water used was 15 mL. The foamed copper used was pretreated. The pretreatment process was as follows: the foamed copper was placed in an HCl solution, ultrasonically treated, washed several times with deionized water and ethanol, and then dried. The concentration of the HCl solution used in the pretreatment was 0.1 mol / L, the ultrasonic time was 15 min, the drying temperature was 60℃, and the drying time was 2 h. The selected foamed copper had a pore density of 110 ppi, a diameter of 18 mm, and a thickness of 1.8 mm.

[0051] The hydrothermal reaction is specifically as follows:

[0052] The mixed solution was mixed with pretreated copper foam and then transferred to a high-pressure reactor with a polytetrafluoroethylene liner. The reaction temperature was controlled at 110℃ and the reaction time was 10h. After the reaction was completed, the mixture was cooled to room temperature, washed with deionized water and dried at 60℃ for 2h.

[0053] (2) Co-modified@CF was pyrolyzed in an inert atmosphere to obtain a black flake sample CoO@CF, wherein the inert atmosphere was nitrogen atmosphere, the pyrolysis temperature was 320℃, the pyrolysis time was 1h, and the pyrolysis heating rate was 3℃ / min.

[0054] (3) Dissolve 2-MIM in deionized water and anhydrous ethanol to obtain a mixed solution. Add CoO@CF to the above mixed solution for soaking treatment. After soaking, take it out, wash and dry it to obtain ZIF-67@CF-H. The molar ratio of deionized water to ethanol is 1:1, the soaking time is 12h, the drying temperature is 60℃, and the drying time is 2h. In this example, the amount of 2-MIM used is 2mmol, the amount of deionized water used is 5mL, and the amount of anhydrous ethanol used is 5mL.

[0055] (4) ZIF-67@CF-H was calcined in air to obtain a dodecahedral Co3O4 particle array foam copper-based catalyst, wherein the calcination temperature was 350℃, the calcination time was 3h, and the calcination heating rate was 3℃ / min.

[0056] Example 3

[0057] A method for preparing a dodecahedral Co3O4 particle array foam copper-based catalyst includes the following steps:

[0058] (1) Dissolve Co(NO3)2·6H2O, NH4F and CH4N2O in deionized water to obtain a mixed solution. Transfer the copper foam and the above mixed solution to a reactor for hydrothermal reaction to obtain a pink flake sample Co-modified@CF.

[0059] The molar ratio of Co(NO3)2·6H2O, NH4F, and CH4N2O added was 1:4.5:5.5. In this embodiment, the amount of Co(NO3)2·6H2O used was 2 mmol, the amount of NH4F used was 8 mmol, the amount of CH4N2O used was 10 mmol, and the amount of deionized water used was 15 mL. The foamed copper used was pretreated. The pretreatment process was as follows: the foamed copper was placed in an HCl solution, ultrasonically treated, washed several times with deionized water and ethanol, and then dried. The concentration of the HCl solution used in the pretreatment was 0.1 mol / L, the ultrasonic time was 15 min, the drying temperature was 60℃, and the drying time was 2 h. The selected foamed copper had a pore density of 110 ppi, a diameter of 18 mm, and a thickness of 1.8 mm.

[0060] The hydrothermal reaction is specifically as follows:

[0061] The mixed solution was mixed with pretreated copper foam and then transferred to a high-pressure reactor with a polytetrafluoroethylene liner. The reaction temperature was controlled at 130℃ and the reaction time was 14h. After the reaction was completed, the mixture was cooled to room temperature, washed with deionized water and dried at 60℃ for 2h.

[0062] (2) Co-modified@CF was pyrolyzed in an inert atmosphere to obtain a black flake sample CoO@CF, wherein the inert atmosphere was nitrogen atmosphere, the pyrolysis temperature was 360℃, the pyrolysis time was 1h, and the pyrolysis heating rate was 3℃ / min.

[0063] (3) Dissolve 2-MIM in deionized water and anhydrous ethanol to obtain a mixed solution. Add CoO@CF to the above mixed solution for soaking treatment. After soaking, take it out, wash and dry it to obtain ZIF-67@CF-H. The molar ratio of deionized water to ethanol is 1:1, the soaking time is 12h, the drying temperature is 60℃, and the drying time is 2h. In this example, the amount of 2-MIM used is 2mmol, the amount of deionized water used is 5mL, and the amount of anhydrous ethanol used is 5mL.

[0064] (4) ZIF-67@CF-H was calcined in air to obtain a dodecahedral Co3O4 particle array foam copper-based catalyst, wherein the calcination temperature was 350℃, the calcination time was 3h, and the calcination heating rate was 3℃ / min.

[0065] Cobalt was grown on the surface of copper foam using a hydrothermal method to obtain cobalt-modified copper foam. CoO-supported copper foam was obtained through pyrolysis in a nitrogen atmosphere. ZIF-67, with a transition metal Co as the central atom, was generated by combining with 2-methylimidazolium (2-MIM). Finally, copper foam-based catalysts with a dodecahedral Co3O4 particle array were obtained by calcination in an air atmosphere. The catalyst surface has a dodecahedral Co3O4 particle array, and due to specific morphology control, it possesses a large specific surface area, pore volume, and pore size. Simultaneously, this method fosters strong metal-support interactions between the active material and the support, enhancing the catalyst's redox capacity and surface reactive oxygen species, resulting in excellent performance in the catalytic combustion of toluene gas.

[0066] Comparative Example 1

[0067] The preparation method of Co3O4@CF-E catalyst includes the following steps:

[0068] (1) The copper foam discs (pore density of 110 ppi, diameter of 18 mm, and thickness of 1.8 mm) were placed in a 0.1 mol / L HCl solution and sonicated for 15 min. Then they were washed several times with anhydrous ethanol and deionized water. Finally, the pretreated copper foam was dried at 60 °C for 2 h.

[0069] (2) Electrochemical deposition was performed on an electrochemical workstation using a three-electrode system. Copper foam, Ag / AgCl, and graphite sheets were used as the working electrode, reference electrode, and counter electrode, respectively. Electrochemical deposition was performed by cyclic voltammetry (between -0.6 V and -1.60 V relative to Ag / AgCl) with 60 mL of 0.1 mol / L Co(NO3)2 solution at a scan rate of 10 mV / s for four cycles. Subsequently, the sample was washed with DI water and dried at 80 °C, named Co(OH)2@CF.

[0070] (3) Immerse Co(OH)2@CF in 10 mL of deionized water containing 2 mmol of 2-MIM for 12 h. Remove, wash with deionized water and dry to obtain ZIF-67@CF-E.

[0071] (4) ZIF-67@CF-E was calcined in air at a heating rate of 3℃ / min to 350℃ and continued for 3h to obtain Co3O4@CF-E catalyst.

[0072] Comparative Example 2

[0073] The preparation method of Co3O4 / CuO@CF catalyst includes the following steps:

[0074] (1) The copper foam discs (pore density of 110 ppi, diameter of 18 mm, and thickness of 1.8 mm) were placed in a 0.1 mol / L HCl solution and sonicated for 15 min. Then they were washed several times with anhydrous ethanol and deionized water. Finally, the pretreated copper foam was dried at 60 °C for 2 h.

[0075] (2) CuO@CF was obtained by calcining copper foam at 400°C for 4 hours in air at a heating rate of 3°C / min.

[0076] (3) Immerse CuO@CF in 10 mL of deionized water containing 8 mmol of 2-MIM for 1 h. Then add 10 mL of 0.2 mol / L Co(NO3)2 solution to the above solution and let it stand for 12 h. Remove it, wash it with deionized water, and dry it at 80 °C. ZIF-67 / CuO@CF is obtained.

[0077] (4) ZIF-67 / CuO@CF was calcined in air at a heating rate of 3℃ / min to 350℃ and continued for 3h to obtain Co3O4 / CuO@CF catalyst.

[0078] Comparative Example 3

[0079] The preparation method of Co3O4 / CF catalyst includes the following steps:

[0080] (1) The copper foam discs (pore density of 110 ppi, diameter of 18 mm, and thickness of 1.8 mm) were placed in a 0.1 mol / L HCl solution and sonicated for 15 min. Then they were washed several times with anhydrous ethanol and deionized water. Finally, the pretreated copper foam was dried at 60 °C for 2 h.

[0081] (2) Dissolve 2 mmol of Co(NO3)2·6H2O in 20 mL of deionized water. Then, immerse the copper foam in the above solution and let it stand for 12 h. Remove it, wash it with deionized water and dry it at 80 °C to obtain Co(NO3)2 / CF.

[0082] (3) Co(NO3)2 / CF was calcined in air at a heating rate of 3℃ / min to 350℃ for 3h to obtain Co3O4 / CF catalyst.

[0083] Comparative Example 4

[0084] The preparation method of CF catalyst includes the following steps:

[0085] (1) The copper foam discs (pore density of 110 ppi, diameter of 18 mm, and thickness of 1.8 mm) were placed in a 0.1 mol / L HCl solution and sonicated for 15 min. Then they were washed several times with anhydrous ethanol and deionized water. Finally, the pretreated copper foam was dried at 60 °C for 2 h.

[0086] (2) The pretreated copper foam was calcined in air at a heating rate of 3℃ / min to 350℃ and continued for 3h to obtain the CF catalyst.

[0087] The conversion rate of catalysts prepared by various methods in the catalytic combustion of toluene as a function of temperature is shown in the following figures. Figure 1 As shown in the figure, the dodecahedral Co3O4 particle array foam copper-based catalyst is represented by Co3O4@CF-H.

[0088] The temperatures (T0) corresponding to the 20%, 50%, and 90% conversion of p-toluene with different foamed copper-based catalysts at a mass hourly space velocity (WHSV) of 15000 mL / (g·h) were determined. 20 T 50 T 90 ), as shown in Table 1 below.

[0089] Table 1. Reactor temperatures (T) corresponding to toluene conversion rates of 20%, 50%, and 90% for each catalyst. 20 T 50 T 90 ) Example 1 Toluene 205 20 Comparative Example 1 Toluene 209 20 Comparative Example 2 Toluene 225 20 Comparative Example 3 Toluene 237 20 Comparative Example 4 Toluene 258 20 Example 1 Toluene 211 50 Comparative Example 1 Toluene 219 50 Comparative Example 2 Toluene 239 50 Comparative Example 3 Toluene 263 50 Comparative Example 4 Toluene 295 50 Example 1 Toluene 219 90 Comparative Example 1 Toluene 232 90 Comparative Example 2 Toluene 249 90 Comparative Example 3 Toluene 300 90 Comparative Example 4 Toluene 336 90

[0090] As shown in Table 1, the reactor temperatures corresponding to the catalyst prepared in Example 1 when the conversion rate of toluene reaches 20%, 50%, and 90% are 205℃, 211℃, and 219℃, respectively. These temperatures are the lowest compared to those of Comparative Examples 1, 2, 3, and 4 when the conversion rate of toluene reaches 20%, 50%, and 90%. Therefore, the catalyst prepared in Example 1, namely the dodecahedral Co3O4 particle array foam copper-based catalyst, has a better effect on the catalytic combustion of toluene.

[0091] The effects of different mass hourly space velocities (WHSV) on the catalytic activity of dodecahedral Co3O4 particle array foam copper-based catalysts for toluene are shown in Table 2 below:

[0092] Table 2. Effects of different mass space velocities (WHSV) on the catalytic activity of dodecahedral Co3O4 particle array foam copper-based catalyst for toluene. Example 1 15000 194 208 218 Example 1 30000 200 211 223 Example 1 45000 207 215 232 Example 1 60000 209 220 234

[0093] Mass hourly space velocity (MHSV) is the ratio of the mass of feed to the mass of catalyst per unit time, reflecting the residence time of the material in the catalyst bed. Table 2 shows that the dodecahedral Co3O4 particle array foam copper-based catalyst prepared in Example 1 exhibits different catalytic activities towards toluene at different MHSVs when achieving toluene conversion rates of 20%, 50%, and 90%. At a toluene conversion rate of 20%, a higher MHSV results in higher catalyst activity. Similarly, at toluene conversion rates of 50% and 90%, a higher MHSV also results in higher catalyst activity.

[0094] Figure 2 Long-term stability tests were conducted on the dodecahedral Co3O4 particle array foam copper-based catalyst. The results showed that at a mass hourly space velocity (MHSV) of 15000 mL / (g·h), the catalyst maintained approximately 100% of its p-toluene catalytic activity at 220℃ for 50 hours, exhibiting excellent catalytic activity without any decrease. Furthermore, when the temperature was lowered and maintained at 205℃, the catalyst's catalytic activity remained at approximately 40% for 50 hours, without any decline. Overall, the catalyst demonstrated excellent catalytic activity.

[0095] Figure 3 Cyclic stability testing was conducted on the dodecahedral Co3O4 particle array foam copper-based catalyst. It can be seen that after five consecutive cycles, the catalyst's catalytic activity towards toluene did not show significant change, indicating that the catalyst possesses excellent cyclic stability.

[0096] Figure 4-6 The image shows a SEM image of a dodecahedral Co3O4 particle array foam copper-based catalyst. Dodecahedral particles are clearly visible on its surface, indicating successful loading of ZIF-67-derived Co3O4. Furthermore, the Co3O4 oxide obtained after calcination retains the regular morphology of ZIF-67 well.

[0097] Figure 7-8 This is a SEM image of the CF catalyst. Figure 4 and Figure 7 As can be seen, the framework of the CF catalyst is smoother than that of the dodecahedral Co3O4 particle array foam copper-based catalyst, which further proves that the active material was successfully loaded on the dodecahedral Co3O4 particle array foam copper-based catalyst. Figure 7 The porous structure on the surface of the CF catalyst is considered to be a result of acid etching during pretreatment, which is beneficial for increasing the specific surface area.

[0098] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a dodecahedral Co3O4 particle array foam copper-based catalyst, characterized in that, Includes the following steps: (1) Dissolve Co(NO3)2·6H2O, NH4F and CH4N2O in deionized water to obtain a mixed solution. Transfer the copper foam and the above mixed solution to a reactor for hydrothermal reaction to obtain Co-modified@CF; The hydrothermal reaction is specifically as follows: the mixed solution is mixed with pretreated copper foam and then transferred to a high-pressure reactor with a polytetrafluoroethylene liner. The reaction temperature is controlled at 110~130 ℃ and the reaction time is 10~14h. After the reaction is completed, the mixture is cooled to room temperature, washed with deionized water and dried at 60 ℃ for 2h. (2) Co-modified@CF is pyrolyzed under an inert atmosphere to obtain CoO@CF; The inert atmosphere is nitrogen, the pyrolysis temperature is 320~350 ℃, the pyrolysis time is 1 h, and the pyrolysis heating rate is 3℃ / min; (3) Dissolve 2-MIM in deionized water and anhydrous ethanol to obtain a mixed solution. Add CoO@CF to the above mixed solution for soaking treatment. After soaking, take it out, wash and dry it to obtain ZIF-67@CF-H. (4) ZIF-67@CF-H was calcined in air to obtain a dodecahedral Co3O4 particle array foam copper-based catalyst.

2. The method for preparing the foamed copper-based catalyst of dodecahedral Co3O4 particle array as described in claim 1, characterized in that, In step (1), the molar ratio of the added amounts of Co(NO3)2·6H2O, NH4F and CH4N2O is 1:3.5~4.5:4.5~5.

5.

3. The method for preparing the foamed copper-based catalyst of dodecahedral Co3O4 particle array as described in claim 1, characterized in that, The foamed copper used in step (1) is pretreated foamed copper, and the pretreatment specifically includes: The copper foam was placed in an HCl solution, sonicated, washed several times with deionized water and ethanol, and then dried.

4. The method for preparing the foamed copper-based catalyst of dodecahedral Co3O4 particle array as described in claim 3, characterized in that, The pretreatment used an HCl solution with a concentration of 0.1 mol / L, an ultrasonic time of 15 min, a drying temperature of 60℃, and a drying time of 2 h.

5. The method for preparing the foamed copper-based catalyst of dodecahedral Co3O4 particle array as described in claim 1, characterized in that, The inert atmosphere in step (2) is nitrogen atmosphere, the pyrolysis temperature is 320~350 ℃, the pyrolysis time is 1 h, and the pyrolysis heating rate is 3℃ / min.

6. The method for preparing the foamed copper-based catalyst of dodecahedral Co3O4 particle array as described in claim 1, characterized in that, In step (3), the molar ratio of deionized water to ethanol is 1:1, the soaking time is 12 h, the drying temperature is 60 ℃, and the drying time is 2 h.

7. A foamed copper-based catalyst of dodecahedral Co3O4 particle array, prepared by the method described in any one of claims 1-6.

8. The application of the foamed copper-based catalyst of the dodecahedral Co3O4 particle array as described in claim 7 in the catalytic combustion of toluene gas.

Citation Information

Patent Citations

  • Method for preparing toluene catalytic combustion monolithic catalysts and application

    CN105688904A

  • Integral composite catalyst for catalytic combustion of VOCs (volatile organic compounds) as well as preparation method and application

    CN106902838A

  • Preparation of foam metal-based monolithic catalyst and application of foam metal-based monolithic catalyst in photo-thermal degradation of VOCs (Volatile Organic Compounds)

    CN115845850A

  • Catalyst as well as preparation method and application thereof

    CN117463372A